2009
DOI: 10.1186/1471-2288-9-58
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Activity Questionnaire for Adults and Adolescents (AQuAA)

Abstract: BackgroundAccurate measures of physical activity are highly needed. We evaluated the test-retest reliability and construct validity of the self-report Activity Questionnaire for Adults and Adolescents (AQuAA). The AQuAA is a commonly used questionnaire in Dutch youth.MethodsIn the test-retest reliability study, 53 adolescents and 58 adults completed the AQuAA twice, with an interval of two weeks. In the validity study, 33 adolescents and 47 adults wore an accelerometer (Actigraph) during two weeks, and subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
103
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(114 citation statements)
references
References 17 publications
6
103
4
Order By: Relevance
“…However, most of the studies referred to used subjective assessment measures of PA that may over-estimate the time spent in MVPA (Chinapaw et al, 2009). Moreover, subjective methods may not have the ability to account for activities of less than 10 minutes in duration, while objective measures include mostly all physical activity, independently of its length (Tudor-Locke & Myers, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the studies referred to used subjective assessment measures of PA that may over-estimate the time spent in MVPA (Chinapaw et al, 2009). Moreover, subjective methods may not have the ability to account for activities of less than 10 minutes in duration, while objective measures include mostly all physical activity, independently of its length (Tudor-Locke & Myers, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, accelerometers are not able to measure precisely upper body movements, weight-bearing activities, cycling and swimming 10,29 . Cut-off points from accelerometer-calibration studies needed to categorize counts into levels of intensity are not validated for pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…ICC values indicated good to excellent reliability among all students of grade 8 (mean age 13?3 years) for screen behaviour (ICC 5 0?78 for girls and ICC 5 0?90 for boys), while our study showed moderate to good reliability values for screen behaviour (ICC 5 0?43-0?66). A study by Chinapaw et al (30) (31) . Our study showed good to excellent test-retest reliability (ICC/k 5 0?00-0?98 and agreement 5 37-99 %) and mixed values for the construct validity study on physical activity items (ICC/k 5 0?07-0?96 and agreement 5 28-100 %).…”
Section: Discussionmentioning
confidence: 99%